Representación de mural “Yanantin Pacha” en el estilo surrealista y la percepción de la Cosmovisión Andina de los estudiantes del Instituto Tecnológico Superior Jatun Yachay Wasi, En la provincia de Chimborazo, cantón Colta, periodo mayo – octubre 2023 - Copa Pomaquero, Edison Joel (2024)
This study focuses on the creation of a surrealist mural painting titled "Yanantin Pacha," as well as the students' perceptions of Andean cosmovision at the Instituto Tecnológico Superior Jatun Yachay Wasi in Colta, Chimborazo. The goal is to examine how this mural uses surrealistic symbols and artistic aspects to portray the Andean culture's dualistic and complimentary vision of the universe.Surrealism, as an avant-garde movement, is distinguished by its exploration of the limits of the human being and inner expression, often through illogical and scrambled forms. These dreamlike elements are incorporated into the creation of the mural, providing a unique interpretation that connects with the perception of the Andean peoples. The Andean cosmovision, which fuses the physical with the spiritual, significantly influences our perception and understanding of the world. Culture and individual identity play an essential role, since they influence the formation of knowledge and opinions, and thus the interpretation of other artistic manifestations.The research methodology included qualitative and quantitative methods, such as an iconographic and iconological analysis of the mural to identify symbols, shapes, colors and techniques used. In addition, a survey of students was carried out to evaluate their appreciation of the mural and interviews with teachers at the National University of Chimborazo.The results indicate that the mural manages to represent the Andean cosmovision through surrealist language, incorporating elements of the Andean world. The majority of those surveyed recognized the cultural and historical value of the mural as an artistic expression that promotes Andean cultural identity.